It's All About Timing: Age‐Dependent Consequences of Founder Exits and New Member Additions. (15th January 2015) - Guenther, Christina; Oertel, Simon; Walgenbach, Peter
Abstract : This article explores the effects of changes in the initial venture team on a firm's failure risk by considering firm age. The results show that founder exits are especially critical for firm survival in the first years of a firm's existence, whereas the entry of a new team member is more beneficial in later years. Further, an investigation of multiple founder exits shows that the time that elapses between two exits has a U‐shaped relationship with a firm's hazard risk. Discussing these findings in terms of imprinting and the liability of newness, we contribute to a more comprehensive understanding of venture team dynamics and firm survival.